Game-theory analysis of multi-processor schedulers. Simulation model - Ignatenko, O.P.; Odobesku, V.I. (PROBLEMS IN PROGRAMMING, 2018)
This paper deals with a game model of users performing parallel computing in a heterogeneous multiprocessor system. The proposed approach is applied to the problem of matrix multiplication on the system with the scheduler of min-min type. The user’s action is to choose the size of the blocks into which the matrix is cut. Each user tries to optimize own finish time, which leads to conflict. Using the game theoretic approach, we build game model and found the conditions of Nash equilibrium existence in the scheduling game of two users. Simulation program was built to provide experimental data.Problems in programming 2018; 2-3: 075-082